GURU SEBAGAI DETERMINAN PENCAPAIAN PENDIDIKAN YANG MERATA: KAJIAN PUSTAKA KRITIS DI INDONESIA - Fathiyyatil Faizah; Dwi Cahyaningdyah (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
Equitable education is the cornerstone for achieving social justice and enhancing the competitiveness of national human resources. Despite government efforts to expand access to education, regional quality disparities remain a fundamental issue that has yet to be fully resolved. This article aims to critically examine the position of teacher quality as a key determinant in achieving equitable education in Indonesia. Using a library research approach, this article analyzes various academic literatures, policy documents, and relevant research reports. The findings indicate that disparities in teacher competence and distribution constitute the main node that widens the educational quality gap between urban and rural areas, particularly in underdeveloped, frontier, and outermost (3T) regions. The low quality of Teacher Training Institutions (LPTK), recruitment mechanisms that have not been fully merit-based, and limited programs for continuous professional development further exacerbate this condition. Government policies on teacher redistribution, accelerated certification, and welfare improvement show signs of progress, but their implementation still faces various structural and cultural challenges. This article recommends a holistic and contextual approach that integrates the strengthening of teacher competence, equitable distribution, and simultaneous reform of the educational human resource management system.